Estudo comparativo e ecológico de ectoparasitos branquiais de Cichla kelberi Kullander & Ferreira, 2006 (Perciformes, Cichlidae) dos reservatórios de Itaipu-PR e Lajes-RJ, Brasil. - Yamada, Fábio Hideki (2008)
Eighty gills of Cichla kelberi were analyzed, being 41 collected monthly from Itaipu reservoir between February and November 2006, and 39 collected bimonthly from Lajes reservoir between July 2005 and December 2006. The purpose was to compare and evaluate similarities and differences between the main aspects of the ectoparasitary ecology of C. kelberi from two populations of different basins. The parasite richness of the fish from Itaipu reservoir varied from 1 to 5, while the fish from Lajes reservoir ranged from 1 to 3. Both populations of parasites showed concentration for dominance (C>0.25), and Ascocotyle sp. and Sciadicleithrum ergensi were the dominant parasites in Itaipu and Lajes reservoirs, respectively. The community of gill parasites of C. kelberi from both localities showed a typical pattern of overdispersion or aggregation of parasitic systems. Interspecific associations were observed between pairs of species co-occurring and covariation of abundance of parasites for the hosts in both reservoirs. The results demonstrated no significant differences in the prevalence and the abundance of parasites between males and females hosts from both places. There were significant correlations between the standard length and abundance and prevalence of parasitism and some significant correlations between the relative condition factor (Kn) and abundance of infestation of some parasites. Only S. ergensi, a parasite of fish from Lajes, showed significant positive correlation between abundance of parasitism and the hepatosomatic relation (HSR). There was a seasonal variation in levels of abundance with the highest values recorded in winter and autumn, in both places. Immature individuals showed levels of parasitism significantly lower for some species of parasites. The infracommunities of gill parasites demonstrated a high similarity of the composition between localities, and only the fish from Itaipu reservoir showed significant positive correlation between the standard length and diversity.